Cognitive Remediation Game of Selecting Tools Independently for Mentally Disordered Patients - Isnanda, Reza Giga; Yosa, Muhammad Ferdy; Setiawan, Asep (Emerging Information Science and Technology, 2024)
Cognitive impairment is one of the negative effects of schizophrenia. To treat this, cognitive remediation could serve as an option to improve the cognitive performance of the sufferers. In this line, Doctor Herdaetha developed a computer-based game module to assist psychiatrists in performing cognitive remediation treatment during the recovery period of patients. However, patients could not utilize the game module without the assistance of psychiatrists, making it ineffective and inefficient. Given these considerations, a mobile Selecting Tool game was created as an independent cognitive remediation medium for schizophrenia patients during their recovery period. The game was created using a waterfall model and involved multiple review and discussion sessions with psychiatrists. The results revealed that the game was well-functioning and could be played independently.